Data from: Kin grouping is insufficient to explain the inclusive fitness gains of conspecific brood parasitism in the common eider - Hervey, Samuel; Barnas, Andrew; Stechmann, Tanner; Rockwell, Robert; Ellis-Felege, Susan; Darby, Brian (Zenodo, 2019)
Conspecific brood parasitism allows females to exploit other females' nests and enhance their reproductive output. Here, we test a recent theoretical model of how host females gain inclusive fitness from brood parasitism. High levels of relatedness between host and parasitizer can be maintained either by; 1) kin recognizing and parasitizing each other as a form of cooperative breeding or 2) natal philopatry and nest site fidelity facilitating the formation of kin groups increasing the probability of parasitism between relatives nesting in close proximity. To address these two hypotheses we genotyped feathers and hatch membranes of common eiders (Somateria mollissima) from western Hudson Bay, using a non-invasive sampling methodology. We found that most instances of brood parasitism do result in inclusive fitness gains. However, a greater inclusive fitness was gained toward the host when she was parasitized by individuals with no nest of their own compared to those that parasitize and nest. Further, females with failed nests moved an average of 492 meters from their previous years nest site, while successful females only moved an average of 13 meters. Therefore, we observed host-parasite relatedness can occur at levels higher than would be expected by chance even in the absence of kin grouping suggesting that closely related females nesting near one another is not essential to maintain high host-parasitizer relatedness. In addition, kin grouping is only a transient phenomenon that cannot occur every year due to the propensity for females of failed nests to nest farther away from their nest site in subsequent years than females with successful nests, which provides support for kin recognition as a more likely mechanism to maintain high host-parasitizer relatedness over time. Hervey2019AlleleNames FastA-formated file of allele names (as in "Hervey2019EiderGenotypes.csv") and their sequences. Allele names include the locus, length, and variant. For example, allele "Sfi01_120_A" is from locus "Sfi01", has length ...